Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products